Life cycle assessment of facile applicable biodiesel production - Mohamed A. Hanafy; Rehab M. Ali; Abdallah S. Elgharbawy; Ahmed I. Osman; Mohamed A. Farrag; Abdulaziz H. Al-Anazi (South African Journal of Chemical Engineering)
Biodiesel is crucial for mitigating fossil fuel depletion and reducing environmental impacts. Herein, this approach represents a life cycle assessment (LCA) of biodiesel production from waste cooking oil (WCO) utilizing potassium carbonate (K2CO3) as a heterogeneous catalyst instead of potassium hydroxide (KOH), which is the most used catalyst in industry. However, KOH requires a 20% methanol and a 66% reaction time, higher than K2CO3. Besides, KOH is used once, and produces impure biodiesel and glycerol. While K2CO3 can be used, recovered and reused twice, which decreases the net required catalyst amount without a significant decrease in biodiesel production yield, decreases the environmental burdens, and produces purer products. When using WCO or high free fatty acid (FFA) oils, K2CO3 has the advantage of effective direct transesterification, while KOH requires post-treatment process (esterification), which means extra usage of methanol besides the acid catalyst, which is commonly H2SO4, to decrease the FFA content and avoid the saponification reaction. Therefore, this research aims to quantify the environmental burdens of biodiesel production and compare the performance of K2CO3 with that of conventional KOH. Using the ReCiPe method in SimaPro 9.5 software, the LCA adheres to ISO 14040 and 14044 standards. Key findings indicate significant impacts in climate change (0.274 kg CO2,eq), human non-carcinogenic toxicity (0.12 kg 14-DCBeq), terrestrial ecotoxicity (0.536 kg 14-DCBeq), and fossil resource scarcity (0.183 kg oileq). Methanol and K2CO3 are identified as major contributors to environmental burdens. In contrast, KOH demonstrates a less environmental impact compared to K2CO3. The economic study revealed that, for producing 250 thousand tons of biodiesel per year, the total CAPEX needed to build up the plant is around 12 M$ for both catalysts. The results proved that using K2CO3 leads to higher net profits. The study revealed that the biodiesel plant would achieve a remarkable net profit using any type of catalyst, with an advantageous economic indicator for K2CO3 over KOH, proving the high profitability of using K2CO3 as a catalyst.